THE CORRELATION BETWEEN ENGLISH VERB TENSE MASTERY AND ENGLISH WRITING ABILITY - HERY KURNIAWAN AKHMAD IKHSAN (Universitas Halu Oleo, 2023)
Good English writing needs adequate mastery of grammatical structure. This study examine how the English verb tense mastery and the English writing ability are correlated each other by using objective tests and composition tests applied to 57 students of a random sample. Descriptive analysis and inferential statistics, Pearson Product Moment Test, were calculated on the corrected test data. For the descriptive analysis, the English verb tense mastery test showed mean of 18.6491, median of 19.0000, mode of 23.000, and SD of 4.47809. The analysis of results of the tests of English writing ability showed mean of 123.4035, median of 121.0000, mode of 153.00, and SD of 29.62254. The mean of English verb tense mastery of the participants was average to good, and it was good to excellent for the mean of English writing ability. The inferential statistical computation showed that the correlation between English verb tense mastery and English writing ability was positive and significant with a correlation coefficient (r) of 0.416 with a significance level (β) of 0.01. The computation also showed that the correlation between the two variables was linear. Clearly, the findings indicated that the hypothesis of the study was accepted